0842 Episodic loss of consciousness in the toilet. Issue 3 (9th February 2012) - Panicker, J; Mclaughlin, C; Seth, J; Eriksson, S; Fowler, C; Walker, M
Abstract : A 21-year-old student presented with events of loss of consciousness whilst passing urine since the age of nine. After voiding a small quantity of urine, she would lose awareness and fall. She could abort these episodes by passing a slow and interrupted urine stream. To avoid these events she voided infrequently and avoided public toilets. She also had overactive bladder symptoms and experienced nocturnal incontinence. Routine investigations were normal. Initial telemetry study was normal but did not record events. When repeated, she was asked specifically to void freely without controlling her stream. Two events were recorded, lasting 110 and 30 s. Semiology was an initial warning (a shock), a tonic component mainly of the right side of the body, left hand automatisms and multifocal jerks. Event 1 evolved into bilateral limb posturing and clonic jerking. EEG revealed normal background activity and occasional left frontal slowing. Post event 1 the background was flat, followed by high amplitude slowing with a left hemispheric emphasis. There was tachycardia prior to the first event but blood pressure remained stable. These features suggested that she has micturition-induced reflex epilepsy. MRI brain was normal and she was started on Lamotrigine. Additionally, urodynamics demonstrated detrusor overactivity and she is on Tolterodine. Micturition-induced epilepsy is a rare type of reflex epilepsy with only seven cases reported in the literature. The patient learnt a complex behaviour to avoid events. This case is unique with the additional finding of detrusor over activity, and management of both problems was addressed.